Structural basis of the specificity of USP18 toward ISG15 - Basters, Anja (Nat Struct Mol Biol, 2017)
Protein modification by ubiquitin and ubiquitin-like modifiers (Ubls) is counteracted by ubiquitin proteases and Ubl proteases, collectively termed DUBs. In contrast to other proteases of the ubiquitin-specific protease (USP) family, USP18 shows no reactivity toward ubiquitin but specifically deconjugates the interferon-induced Ubl ISG15. To identify the molecular determinants of this specificity, we solved the crystal structures of mouse USP18 alone and in complex with mouse ISG15. USP18 was crystallized in an open and a closed conformation, thus revealing high flexibility of the enzyme. Structural data, biochemical and mutational analysis showed that only the C-terminal ubiquitin-like domain of ISG15 is recognized and essential for USP18 activity. A critical hydrophobic patch in USP18 interacts with a hydrophobic region unique to ISG15, thus providing evidence that USP18's ISG15 specificity is mediated by a small interaction interface. Our results may provide a structural basis for the development of new drugs modulating ISG15 linkage. SUPPLEMENTARY INFORMATION: The online version of this article (doi:10.1038/nsmb.3371) contains supplementary material, which is available to authorized users.